2008
DOI: 10.1073/pnas.0801802105
|View full text |Cite
|
Sign up to set email alerts
|

ES cell pluripotency and germ-layer formation require the SWI/SNF chromatin remodeling component BAF250a

Abstract: ATP-dependent chromatin remodeling complexes are a notable group of epigenetic modifiers that use the energy of ATP hydrolysis to change the structure of chromatin, thereby altering its accessibility to nuclear factors. BAF250a (ARID1a) is a unique and defining subunit of the BAF chromatin remodeling complex with the potential to facilitate chromosome alterations critical during development. Our studies show that ablation of BAF250a in early mouse embryos results in developmental arrest (about embryonic day 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
326
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(340 citation statements)
references
References 27 publications
12
326
0
2
Order By: Relevance
“…This finding corresponds to a study that showed altered levels of SWI/SNF subunit expression in mouse ES cells with knockout of one or both alleles of ARID1A. 34 Taken together, these data suggest that SMARCB1 and SMARCD3 expression are not independently affected in endometrial cancer, but the expression level may be reduced when the stability of the SWI/ SNF complex is disturbed because of ARID1A loss.…”
Section: Modern Pathology (2013) 26 1525-1535supporting
confidence: 88%
“…This finding corresponds to a study that showed altered levels of SWI/SNF subunit expression in mouse ES cells with knockout of one or both alleles of ARID1A. 34 Taken together, these data suggest that SMARCB1 and SMARCD3 expression are not independently affected in endometrial cancer, but the expression level may be reduced when the stability of the SWI/ SNF complex is disturbed because of ARID1A loss.…”
Section: Modern Pathology (2013) 26 1525-1535supporting
confidence: 88%
“…For example, the SWI/SNF remodeling complex BAF (BRG1-associated factor) promotes iPSC generation by increasing binding of reprogramming factors to the promoters of pluripotent genes [11]. Homozygous knockout or knockdown of any of several BAF subunits results in defects in ESC self-renewal and differentiation, highlighting their critical roles in maintaining the ESC gene expression pattern [10]. Here, we show that NuRD, a well-characterized corepressor complex that represses transcription in a variety of developmental contexts, blocks epigenetic resetting during the transition of somatic cells into iPSCs by silencing some pluripotency-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with epigenetic reprogramming playing a key role in cell-fate conversion, small molecules that target chromatin-modifying enzymes greatly enhance reprogramming efficiency, yielding iPSCs that are similar to ESCs [7][8][9]. An ESC-specific chromatin remodeling complex, esBAF (embryonic stem cell specific Brg/Brahmaassociated factor), has been shown to be important for the maintenance of pluripotency and the differentiation capacity of ESCs [10,11]. However, the epigenetic pathways that orchestrate chromatin remodeling of specific target genes remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A dominant-negative BRG1 allele blocks myeloid differentiation of 32Dcl3 cells (Vradii et al, 2006), whereas loss of BRG1 in keratinocytes results in defects in limb patterning (Indra et al, 2005). Studies in embryonic stem cells have revealed that lack of BAF250 can compromise cell pluripotency and severely inhibit self-renewal, whereas functional BAF250 contributes to the proper expression of numerous genes involved in embryonic stem cell self-renewal, including Sox2, Utf1 and Oct4 (Yan et al, 2008) (Gao et al, 2008). Furthermore, pluripotency defects in BAF250a mutant embryonic stem cells appear to be cell lineage specific (Gao et al, 2008;Yan et al, 2008).…”
Section: The Swi/snf Complex Is Involved In Differentiationmentioning
confidence: 99%
“…Studies in embryonic stem cells have revealed that lack of BAF250 can compromise cell pluripotency and severely inhibit self-renewal, whereas functional BAF250 contributes to the proper expression of numerous genes involved in embryonic stem cell self-renewal, including Sox2, Utf1 and Oct4 (Yan et al, 2008) (Gao et al, 2008). Furthermore, pluripotency defects in BAF250a mutant embryonic stem cells appear to be cell lineage specific (Gao et al, 2008;Yan et al, 2008). Thus, SWI/ SNF activity appears to be essential for differentiation in yeasts, flies and mammals.…”
Section: The Swi/snf Complex Is Involved In Differentiationmentioning
confidence: 99%